AESCHYNITE GROUP MINERALS FROM VISHNEVYE MOUNTAINS (SOUTH URALS) - V.I. Popova; V.A. Popov; A.V. Kasatkin; A.M. Kuznetsov (Минералогия, 2019)
The crystals morphology, mineral assemblages and chemical composition of aeschynite group minerals from the Vishnevye Mountains (South Urals, Russia) are presented. Some veins of syenitic pegmatites host aeschynite-(Ce) and «thoroaeschynite». The calcite-aegirine-feldspar pegmatites and quartz-arfvedsonite veins contain nioboaeschynite-(Ce) and «alumoaeschynite». Aeschynite- (Y) and nioboaeschynite-(Y) are found in annite-feldspar aggregates in assemblage with REE silicates and carbonates. The find of nioboaeschynite-(Y) is first in Russia.